CONCEPT OF "SOUL" IN THE NARRATIVE-FANTASY OF VOLODYMYR ARENIEV "DUSHNYTSIA" - Khorob, S. S. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2019)
Problem setting. Fundamental scientific research on science fiction in contemporary literary criticism is rather an exception than a regularity. For a long time fantasy did not have sufficient scientific support, remaining just a genre of mass culture. However, lately, science fiction is seen not only as something purely entertaining. After all, it gradually develops: from the scientific object of separate researches (M. Nazarenko, A. Niamtsu, S. Oliinyk, O. Stuzhuk, etc.) to the theme of the great conference “Slavic science fiction” at Taras Shevchenko Kyiv National University and later to the constantly acting (from 2015) research center of literature on fantasy at Taras Shevchenko Institute of Literature in National Academy of Sciences of Ukraine. There is also a trend from a single research to system ones. Therefore, in modern study of literature, the situation has improved considerably concerning proper understanding of this problem, but many aspects of science fiction need to be scientifically substantiated and explored. Analysis of the research. In our opinion among all modern Ukrainian fantasy writers special attention deserves Volodymyr Areniev (Volodymyr Puzii). However, there are few articles about his work. With the exception of the reviews (A. Rybalka on Bukvoiid, A. Shtefan on Chitomo or V. Chernyshenko on the Litaccent) or tangentially to a certain theme (Ovdiichuk L. “Chronotop as a genre factor in modern science fiction and fantasy for children”, Oliinyk S. “Book image in the fantasy world”, as an independent object, appeared in the researches of Oles Stuzhuk and Solomiia Khorob. Therefore, we see the actuality of this scientific article. Goal. To analyze the novel “Dushnytsa” by Volodymyr Areniev in terms of the functioning of the concept “soul”, which appears to be central in this work. It is also necessary to pay attention to the genre peculiarities of the existence of fantasy in the work of the chosen writer.